ANALISIS ASAS KEADILAN PADA PEMBAGIAN HARTA WARISAN MENURUT HUKUM ISLAM - Islamiyati Islamiyati (Masalah-Masalah Hukum, 2015)
Al-Qur’an surah An-Nisa’ sentence 11 dan KHI of section 176 explaining that shares of between men and woman is two comparing one. Inheritance Law of principled Islam form proportional justice, and conception distributive justice its meaning a justice passing to each and everyone based by for its service or its rights.But in certain case, portion of division of heritage cannot that way, so long as there is certain reason is which might of according to Islam law, referred as by this of sulh ( settlement by agreement applying).